The Anthropogenic Impact on Indoor Radon Concentrations for Secunda, Mpumalanga Province, South Africa. Issue 2 (August 2021) - le Roux, Rikus; Bezuidenhout, Jacques; Smit, Hennie; Newman, Richard
Abstract : Abstract: Secunda is a town built amid the coalfields of the Mpumalanga province of South Africa. Surrounding the town are 11 coal-fired plants (CFPs) contributing around 59% of the country's energy needs. It is also home to Sasol Synfuels, which produces synthetic gas through coal gasification and natural gas reforming. Coal, like most materials found in nature, contains trace elements of the naturally occurring primordial radionuclides 40 K, 238 U, 232 Th, and their decay products. The milling and combustion of coal in a CFP increases the mass concentration of these trace elements, and the residuals end up on ash heaps as fly ash, bottom ash, and boiler slag. A small percentage of fly ash also ends up in the atmosphere. This paper sets out to determine the anthropogenic impact of the industrial activity on indoor radon in the town of Secunda in the Mpumalanga region of South Africa. Measurements were done in 37 homes during July when higher indoor radon levels are expected due to homes typically being closed due to the low temperatures. The average indoor radon concentration was found to be 76.4 Bq m −3 . This indicates that the fallout from the industrial activity surrounding Secunda does not enhance the emanation of radon. This may be due to the type of activity or the climate and prevailing winds mitigating its indoor build-up. Measurements during the warmer months and in neighboring towns with different industrial activities are required to confirm the trends established by this research.